If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1y = 3 + -3y Solving 7 + -1y = 3 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 7 + -1y + 3y = 3 + -3y + 3y Combine like terms: -1y + 3y = 2y 7 + 2y = 3 + -3y + 3y Combine like terms: -3y + 3y = 0 7 + 2y = 3 + 0 7 + 2y = 3 Add '-7' to each side of the equation. 7 + -7 + 2y = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 2y = 3 + -7 2y = 3 + -7 Combine like terms: 3 + -7 = -4 2y = -4 Divide each side by '2'. y = -2 Simplifying y = -2
| Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 | | 2(f-3)=f+5 | | 100=60a+[40(2a)] | | -9=x(-10/x) | | 18x+6x-4x+2=2x-10x+16 | | 5x+5=4y-23 | | 2/7*3/8 | | Y-2=5(x-1)/3 | | 18-2x=12-5x | | y+w=c | | x^4y^2-4x^2y=0 | | 3x-3y-x^2y=0 | | 3p-7=14 | | 2x-4+45=4x | | 9-1.84= | | 2x-4=8x-2 | | 12/75 | | (11/3)/(3/2) | | x^2+2y^2+3xy=15 | | 2x-e=-5 | | 20x/x^2 | | 4x+8-x-3=2 | | 110=-5x | | 4x+8-3=23 | | 4z^6+7z^3-15=0 |